Disruption of IP3R2-mediated Ca2+ signaling pathway in astrocytes ameliorates neuronal death and brain damage while reducing behavioral deficits after focal ischemic stroke. Issue 6 (December 2015) - Li, Hailong; Xie, Yicheng; Zhang, Nannan; Yu, Yang; Zhang, Qiao; Ding, Shinghua
Graphical abstract: Highlights: IP3 R2 KO mice exhibited normal brain cytoarchitecture, the same densities of mature astrocytes and neurons, the same GFAP and GLT-1 levels as WT mice. IP3 R2 KO mice did not exhibit ATP-induced Ca 2+ waves in vivo in the astrocytic network, but exhibit spontaneous Ca 2+ increases in astrocytic processes. IP3 R2 KO mice had smaller infarction than WT mice in acute and chronic phases of ischemia. These KO mice also exhibited less neuronal apoptosis, reactive astrogliosis, and tissue loss than WT mice. IP3 R2 KO mice exhibited reduced functional deficits after PT. Abstract: Inositol trisphosphate receptor (IP3 R)-mediated intracellular Ca 2+ increase is the major Ca 2+ signaling pathway in astrocytes in the central nervous system (CNS). Ca 2+ increases in astrocytes have been found to modulate neuronal function through gliotransmitter release. We previously demonstrated that astrocytes exhibit enhanced Ca 2+ signaling in vivo after photothrombosis (PT)-induced ischemia, which is largely due to the activation of G-protein coupled receptors (GPCRs). The aim of this study is to investigate the role of astrocytic IP3 R-mediated Ca 2+ signaling in neuronal death, brain damage and behavior outcomes after PT. For this purpose, we conducted experiments using homozygous type 2 IP3 R (IP3 R2) knockout (KO) mice. Histological and immunostaining studies showed that IP3 R2 KO mice were indeed deficient in IP3 R2 in astrocytes and exhibited normal brain cytoarchitecture. IP3 R2 KO mice also had the same densities of S100β+ astrocytes and NeuN+ neurons in the cortices, and exhibited the same glial fibrillary acidic protein (GFAP) and glial glutamate transporter (GLT-1) levels in the cortices and hippocampi as compared with wild type (WT) mice. Two-photon (2-P) imaging showed that IP3 R2 KO mice did not exhibit ATP-induced Ca 2+ waves in vivo in the astrocytic network, which verified the disruption of IP3 R-mediated Ca 2+ signaling in astrocytes of these mice. When subject to PT, IP3 R2 KO mice had smaller infarction than WT mice in acute and chronic phases of ischemia. IP3 R2 KO mice also exhibited less neuronal apoptosis, reactive astrogliosis, and tissue loss than WT mice. Behavioral tests, including cylinder, hanging wire, pole and adhesive tests, showed that IP3 R2 KO mice exhibited reduced functional deficits after PT. Collectively, our study demonstrates that disruption of astrocytic Ca 2+ signaling by deleting IP3 R2s has beneficial effects on neuronal and brain protection and functional deficits after stroke. These findings reveal a novel non-cell-autonomous neuronal and brain protective function of astrocytes in ischemic stroke, whereby suggest that the astrocytic IP3 R2-mediated Ca 2+ signaling pathway might be a promising target for stroke therapy.